1982
DOI: 10.1016/0031-9201(82)90048-6
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetism of the Upper Silurian and Lower Devonian carbonates of New York State: evidence for secondary magnetizations residing in magnetite

Abstract: Paleomagnetic directions for the Upper Silurian and Lower Devonian carbonates of the Helderberg escarpment (New York State) differ from expected Late Silurian and Early Devonian directions for cratonic North America. The mean direction (D = 165°,I =-10°; paleopole at 50°N129°E)is similar to Late Carboniferous and Early Permian results. Negative fold tests, and a lack of reversals, suggest that the magnetization is secondary. However, low coercivities, low blocking temperatures, the thermomagnetic curves (Tc ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…This observation indicates the possibility that the secondary component of the limestone is chemical remanent megnetization. This possible interpretation agrees well with interpretations by SCOTESE et al (1982), SHIBUYA and SASAJIMA (1986), SHIBUYA (1986) andMOREAU et al (1987). SCOTESE et al (1982) reported secondary magnetizations residing in magnetite for Upper Silurian and Lower Devonian limestones.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This observation indicates the possibility that the secondary component of the limestone is chemical remanent megnetization. This possible interpretation agrees well with interpretations by SCOTESE et al (1982), SHIBUYA and SASAJIMA (1986), SHIBUYA (1986) andMOREAU et al (1987). SCOTESE et al (1982) reported secondary magnetizations residing in magnetite for Upper Silurian and Lower Devonian limestones.…”
Section: Discussionsupporting
confidence: 91%
“…This possible interpretation agrees well with interpretations by SCOTESE et al (1982), SHIBUYA and SASAJIMA (1986), SHIBUYA (1986) andMOREAU et al (1987). SCOTESE et al (1982) reported secondary magnetizations residing in magnetite for Upper Silurian and Lower Devonian limestones. The results of thermal demagnetization for the limestones are very similar to our results for the Akiyoshi limestone.…”
Section: Discussionsupporting
confidence: 91%
“…All limestone samples contain a northerly and down magnetization with low unblocking temperatures designated as the A component. The A component is attributed to a viscous remanence of recent origin that is typical of Paleozoic carbonate rocks in the western New York region (Scotese, Van der Voo & McCabe 1982;McCabe et al 1984;Kent 1985). We note, however, that within about one dike width the peak unblocking temperature (200 "C) of this component is appreciably lower than peak viscous remanent magnetization unblocking temperatures (-300 "C) commonly observed in such limestones.…”
Section: Contact Testsmentioning
confidence: 81%
“…The shallowing could be a result of bias by the incomplete removal of the northerly and steep downward A component. The southerly and shallow C component (Dec. = 171.6", Inc. = -10.0"; a95 = 4.0", n = 9) predates dike intrusion and is interpreted as a Late Palaeozoic (Kiaman) secondary magnetization as typically observed in Appalachian limestones and shales(Scotese et al 1982;McCabe et al 1984;Kent 1985). Positive baked contact test in Devonian limestone country rock adjacent to reverse polarity, 15.2 cm wide Portland Point dike.…”
mentioning
confidence: 98%
“…The first references to 'remagnetization' can be found in the 1960s but it is especially from the 1980s that numerous studies about remagnetizations were published (Scotese et al 1982;Kent 1985;Tucker & Kent 1988;McCabe & Elmore 1989). Most of them were performed in sedimentary rocks (limestones, marls or red beds), as identification of remagnetizations is easier when fold-or conglomerate-tests can be performed.…”
mentioning
confidence: 99%